Nationalism at Work: Introducing the “Nationality-Based Organizational Climate Inventory” and Assessing Its Impact on the Turnover Intention of Foreign Employees - Köllen, Thomas (Springer Nature, 2020)
https://doi.org/10.1007/s11575-019-00408-4